Audit Komunikasi Organisasi Wahana Lingkungan Hidup Indonesia (Walhi) Yogyakarta - Dian Ramadani; Puji Lestari; Muhammad Edy Susilo (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2015)
The paper aims to analyze process of communication audit in WALHI Yogyakarta organization to increase organization systems to improve organization effectiveness using information of organization theory and qualitative descriptive method. The research found that the process of implementation communication audit of organization in WALHI Yogyakarta works quite well as demonstrated by the five units of analysis: organization, content of information, management of organization, communication processes or activities of communication, and feedback. Of the five unit of analysis it is found that openness factor vertically or horizontally has a big role in improving the performance of an organization’s success. Another factor is the role of communication technology to simplify and accelerate the delivery of information internally. Media written or printed or electronic media is used in support of this organization. Communication audit implemented in every organization will improve the performance of organization.